MEMBANGUN JIWA KEPEMIMPINAN SISWA YANG VISIONER DAN BERDAYA SAING GLOBAL DI SMK SASMITA JAYA 1 PAMULANG - Yulita Pujilestari; Siti Zubaidah; Edison F.J. Patty; Sri Susanti; Adhitya Agustian Pratama; Diah Nurfatimah; Nunung Iswati; Ruri Puspita Ningsih (Pascasarjana Universitas PTIQ Jakarta, 2025)
21st-century education demands the development of student character that is not only academically intelligent but also possesses a visionary leadership spirit and the ability to compete globally. This article aims to explore strategies and approaches for cultivating student leadership from an early age, with a focus on integrating leadership values, strengthening character, and leveraging global technology. This approach includes curriculum development, extracurricular activities, leadership training, and international collaboration. Using a qualitative-descriptive approach, data were collected through interviews, observations, and documentation related to student development activities. The findings indicate that student leadership is strengthened through the integration of character-based curricula, leadership training, international collaboration, and the use of technology and digitalization. The study concludes that visionary leadership can be instilled through a holistic, contextual, and globally competitive education process. Vocational education plays a crucial role in preparing young generations who are not only technically skilled but also possess strong leadership character and the ability to compete on a global scale.